Heart rate recovery after typical endurance exercise session in athletes - Uusitalo, A. L.; Hoffman, T. A.; Tummavuori, E. A.; Rusko, H. K. (Medicine & Science in Sports & Exercise, 1998)
Heart rate recovery patterns were investigated in endurance athletes (M = 2; F = 3) after three different forms of training; 1) long slow distance work (2-4 hours at <65% VO2max), 2) an intense interval run (5 x 1 km; >90% VO2max), and a control (30-60 minutes; <65% VO2max). Heart rate and heart rate variability were measured during five minutes of supine rest and during five minutes of standing, and heart rate and blood lactate were assessed before and 4, 24, and 48 hours after each form of exercise. The forms of exercise did not change blood lactate levels, heart rates, or heart rate variability. Recovery of heart rates was complete within 24 hours of exercise, and long slow distance work caused the greatest response in heart rate variables. There were great individual differences in all variables especially in heart rate variability. Implication. Heart rate responses differ markedly between individuals however, heart rates recover from endurance exercise within 24 hours but long-slow distance work has the greatest effect on heart rate responses. It is not appropriate to compare heart rate recovery response patterns when forms of endurance exercise differ.